Investigating the effects of COVID-19 on tourism in the G7 countries - Komasi, Hossein; Nemati, Alireza; Hashemkhani Zolfani, Sarfaraz; Williams, Nigel L; Bazrafshan, Ramin (Technological and Economic Development of Economy, 2024)
Natural and human-made crises can significantly impact the development of countries’ tourism industries. The susceptibility of countries to these crises depends on their policies, planning, and management in facing diverse challenges. This article aims to investigate the effects of the COVID-19 pandemic on the tourism industry in G7 countries by comparing rankings and positions on indices in 2016 and 2020. Data collected from the RANking COMparison (RANCOM), Proximity Indexed Value (PIV), and Double Normalization Compromise Ranking of Alternatives from Distance to Ideal Solution (DNCRADIS) models have been utilized for data analysis. The research findings indicate noticeable differences in using different models, as the rankings and positions of G7 countries for the years 2016 and 2020, except for two countries, the United States and France, have been different. The research results demonstrate that the COVID-19 crisis had significant impacts on the tourism industries of G7 countries. Countries like the United States, France, and the United Kingdom appear as leading nations in the tourism industry, while Japan and Canada faced challenges, and Germany and Italy experienced changes in their positions. Based on these results, officials and planners in the tourism industry of G7 countries can make appropriate decisions for the development and improvement of tourism under similar crisis conditions. Moreover, these findings can serve as a valuable guide for other countries in managing similar crises in the tourism industry.